Sikap Wisatawan terhadap Obyek Wisata Taman Kyai Langgeng Magelang - Ira Astriyani; Eka Sudarusman (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2016)
AbstractAn attitude descripbes a person’s relatively consistent evaluations, feelings, and tendencies toward an object or idea. Attitudes put poeple into a frame of mind of liking or disliking things, of moving toward or away from them. Attitude is the one important of the buying process, especialty for psychological factor. Attitude is the result of learning process. An attitude have three componen, and they componen relations each other. They are cognitive, affective, and behavior. Cognitive are knwolegde and belief an object, affective is a tendeny for the object, and behavior is tendency to make action to the object. The object in this reseach is tourism, that is Taman Kyai Langgeng, Magelang. The objective in this reseach want to know consumer attitude. Tourism object must to analys the atributes of an attitude. They are location, services, facility, and the price an object, based on demoghraphy caracteristic.